INVESTIGATION OF THE ROLES OF ATM AND ATR IN TAMOXIFENINDUCED APOPTOSIS IN 4T1 MOUSE BREAST CANCER CELLS: Life Science-Bio Chemistry - HASAN, NAFIS; KURT, ROBERT; SHYAMAL K. MAJUMDAR (International Journal of Life Science and Pharma Research, 2012)
Tamoxifen has long been used as a treatment for advanced and metastatic estrogen receptor positive breast cancer and also for reducing incidences of breast cancer in high-risk populations. Tamoxifen exerts its effects as a selective estrogen receptor modulator (SERM), thus binding to estrogen receptors and inhibiting estrogen activity. But this activity, along with the genotoxic effects of Tamoxifen, results in apoptosis and necrosis of both cancerous and healthy cells. This gives rise to the well-characterized side effects of Tamoxifen such as uterine and endometrial cancers. The major mechanisms of apoptosis by Tamoxifen have already been described in literature, but the ATR-ATM-TP53 pathway has not been reported. The purpose of this study was to investigate the roles of ATR and ATM in Tamoxifen-induced apoptosis of estrogen receptor positive (ER(+)) 4T1 mouse breast cancer cells. The study employs cell growth assays with differential Tamoxifen treatments, silencing of ATR and ATM genes using RNA interference, gene expression analysis using qPCR and also uses post-translational caspase-9 and p38 inhibitors to accomplish its goals. The results of the study show that inhibition of ATR and ATM genes did not significantly increase cell viability in presence of Tamoxifen, contrary to the initial assumptions. This strongly suggests that ATR and ATM do not play a significant role in the Tamoxifen-induced apoptosis of ER(+) 4T1 cells.